Substituição de lactose em pó micronizada por permeado de soro em pó micronizado em leite condensado: efeito sobre a cristalização da lactose, características físico-químicas, reológicas e microbiológicas - Massari, Mariana Riani (2018)
Condensed milk is a very widespread product consumed in Brazil and the world. For their manufacturing the ingredients are a milk, sucrose and micronized lactose, their function is the latest promising crystallization orientated, acting like core, inducing the formation of several crystals small and imperceptible to the palate. The process of ultrafiltration of whey has by protein fraction of the same, resulting in the production of milk rich in lactose and still underutilized by the industry. The test was carried out with the substitution of micronized lactose by serum permeate in micronized, in order to verify its efficiency in the crystallization of lactose in condensed milk. Analyzes of cen-tesimal composition, chemical chemical, microbiological and rheological enzymes were done, such as the size of the lactose crystals of different brands of condensed milk purchased in the local market. Four units were prepared: 01 or control (0.03% commercial anhydrous lactose), 02 (0.03% of micronized whey powder permeate), 03 (0.033% of micronized whey powder permeate) and 04 add of an agent to promote a microcrystallization in triplicate. The formulations were submitted to determination of the centesimal composition, physical-chemical properties, rheological and color anal-ysis; characterization of the average diameter of lactose crystals, microbiological anal-ysis, evaluation of sensorial acceptability. The diameter of lactose crystals under opti-cal microscope, sensorial analysis, rheology and color were evaluated during the use-ful life (7, 15, 30, 60, 90 and 120 days). The format of the lactose crystals were ana-lyzed at 120 scan time in the scanning electron microscope. The results obtained showed that the sugars condensed milk present in the local trade have significant var-iation (p <0.05) in relation to the centesimal composition, especially the parameters fat, pH, acidity, proteins and carbohydrates. The diameters of the lactose crystals and the rheological behavior also presented a lot of variation. The substitution of micronized lactose by permeate of micronized whey powder did not alter the chemical and physical chemical, microbiological and rheological properties in relation to the control. In the sensorial evaluation the treatment 02 presented the best grades. The control treatment obtained the smallest size of crystals in the final product that were maintained during the 120 days of study, presenting uniform characteristics. The treatments with addition of the serum permeate presented with crystal size similar to the control. On the other hand, the crystallization-free treatment showed crystals of much larger sizes. The rhe-ological behavior of the control and treatments with serum permeate showed very sim-ilar values, while the treatment without addition of lactose / permeate presented higher viscosity. The substitution of powdered micronized lactose by powdered whey perme-ate is a good alternative to induce crystallization without affecting physical, chemical, microbiological, sensory and rheological characteristics.